Do Young Employees Satisfy Their Job Under Work Stress and Work-Family Conflict? Evidence from Resorts in Macau - Jinquan Zhou; Bo Wendy GAO; Wenjin He; Gang He (International Journal of Science and Society, 2022)
Young employees currently face vast work stress in their careers triggering conflict between work and family. This paper target to examine how work-family conflict affects job satisfaction and turnover intentions through work stress for younger employees. 450 questionnaires were collected from young dealers who work at six casinos in Macau. The findings show that work-family conflict (WFC) and family-work conflict (FWC) positively affect work stress and turnover intention, but do not directly influence job satisfaction. Work stress negatively affected job satisfaction and positively affected turnover intention, fully negatively mediated WFC and FWC towards job satisfaction, and part positive mediated WFC and FWC towards turnover intention. Work stress can directly influence turnover intention, and job satisfaction partially mediated work stress toward turnover intention. Finally, WFC and FWC will affect turnover intention through work stress on job satisfaction. We also proposed suggestions to improve job satisfaction for young dealers in casino management.